Handbuch ÖPNV. Schwerpunkt Österreich. - (:unkn) unknown (DVV Media Group, 2016)
Alongside a range of various safety measures it was acknowledged that leadership and an open approach to mistakes have a major influence on the safety awareness of each individual driving staff member. The project 'team manager' has set itself the complex task to provide a direct contact person and supervisor with the highest possible availability for each of the 1500 driving staff members within tramway operations of Wiener Linien. The accident rate has decreased drastically since the beginning of the project and proves success.
Leadership and communication with driving staff members.
Keywords: Öffentlicher Verkehr; ÖPNV; Verkehrsverhalten; Mobilität; Verkehrssystem; Verkehrsverbund; Fahrzeug; Wartung; Finanzierung; Barrierefreiheit